Human BCDIN3D Is a Cytoplasmic tRNAHis-Specific 5′-Monophosphate Methyltransferase - Tomita, Kozo; Liu, Yining (Frontiers in Genetics, 2018)
Bicoid interacting 3 domain containing RNA methyltransferase (BCDIN3D) is a member of the Bin3 methyltransferase family and is evolutionary conserved from worm to human. BCDIN3D is overexpressed in breast cancer, which is associated with poor prognosis of breast cancers. However, the biological functions and properties of BCDIN3D have been enigmatic. Recent studies have revealed that human BCDIN3D monomethylates 5'-monophsosphate of cytoplasmic tRNAHis in vivo and in vitro. BCDIN3D recognizes the unique and exceptional structural features of cytoplasmic tRNAHis and discriminates tRNAHis from other cytoplasmic tRNA species. Thus, BCDIN3D is a tRNAHis-specific 5'-monophosphate methyltransferase. Methylation of the 5'-phosphate group of tRNAHis does not significantly affect tRNAHis aminoacylation by histidyl-tRNA synthetase in vitro nor the steady state level or stability of tRNAHis in vivo. Hence, methylation of the 5'-phosphate group of tRNAHis by BCDIN3D or tRNAHis itself may be involved in certain unknown biological processes, beyond protein synthesis. This review discusses recent reports on BCDIN3D and the possible association between 5'-phosphate monomethylation of tRNAHis and the tumorigenic phenotype of breast cancer.